Consumer Behavior towards Decision Making and Loyalty to Particular Brands - Oke, Adunola Oluremi; Kamolshotiros, Parinda; Popoola, Oluwamayowa Yewande; Ajagbe, Musibau Akintunde; Olujobi, Olusola Joshua (International Review of Management and Marketing, 2016)
Currently, consumers pay more attention to their health; there is a growing awareness of health benefits of healthy drinks such as the green tea. Green tea is a popular healthy drink that helps prevent many deadly diseases. There are increasing numbers of green tea manufacturers around the world especially in Thailand. This industry has overwhelmingly expanded due to high consumers demand and purchases. Previous studies show that the market of green tea beverage in Thailand is worth nearly 9,000 million baht. The most popular green tea brand in Thailand known as “Oishi” accounts for over 50% of the total market share and as a result of the growing demand for this product, its market worth and benefits to the consumers, there is need to look at the consumers’ behaviour towards the product. Hence, the purpose of this study is to explore the determinants of consumer behaviour and decision making towards loyalty to Oishi green tea. A survey method using well-constructed questionnaire was administered to 50 consumers. The researchers utilized the Statistical Package for Social Sciences (SPSSversion 19.0) as data analysis tool to run the analysis such as the chi-square and correlation analysis. The findings of this study shows that the factors influencing Thai consumer decisions toward Oishi beverage green tea are perception values (brand awareness, brand association and brand loyalty) and perceived quality. In addition, there is a positive link between decision making and consumer loyalty behaviours which are re-purchasing and word-of-mouth behaviour. This study discovered that apart from the four main factors well-thought-out in the literature review, there are other numerous factors (such as convenience to buy, taste, flavours, price and packaging) that influence consumer decision to buy and consume the Oishi green tea. Based on these findings, this study provides consciousness for further marketing research development and also the strategies for planning an efficient marketing strategy in responding to consumer needs. Keywords: Consumer Behavior; Brand Loyalty; Marketing Strategy; Repeat Purchase JEL Classifications: C91, M3